2018
DOI: 10.1186/s40035-018-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

Divergent topological networks in Alzheimer’s disease: a diffusion kurtosis imaging analysis

Abstract: BackgroundBrain consists of plenty of complicated cytoarchitecture. Gaussian-model based diffusion tensor imaging (DTI) is far from satisfactory interpretation of the structural complexity. Diffusion kurtosis imaging (DKI) is a tool to determine brain non-Gaussian diffusion properties. We investigated the network properties of DKI parameters in the whole brain using graph theory and further detected the alterations of the DKI networks in Alzheimer’s disease (AD).MethodsMagnetic resonance DKI scanning was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
3
12
0
Order By: Relevance
“…It may also be the earliest region susceptible to pathological changes in patients with aMCI/AD (Gordon et al, 2013 ; Luo et al, 2014 ). The detection of reduced MK/CBF in the left Hip is also consistent with the previous results of DKI/ASL perfusion studies (Dai et al, 2009 ; Binnewijzend et al, 2013 ; Gong et al, 2017 ; Cheng et al, 2018 ; Song et al, 2019 ). As a limbic cortical region, the PCC is affected relatively early in the pathological progression to AD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It may also be the earliest region susceptible to pathological changes in patients with aMCI/AD (Gordon et al, 2013 ; Luo et al, 2014 ). The detection of reduced MK/CBF in the left Hip is also consistent with the previous results of DKI/ASL perfusion studies (Dai et al, 2009 ; Binnewijzend et al, 2013 ; Gong et al, 2017 ; Cheng et al, 2018 ; Song et al, 2019 ). As a limbic cortical region, the PCC is affected relatively early in the pathological progression to AD.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous series of studies, patients with aMCI and patients with AD demonstrated aberrant microstructures according to DKI (Struyfs et al, 2015 ; Chen et al, 2017 ; Cheng et al, 2018 ; Song et al, 2019 ) or CBF changes according to ASL (Yoshiura et al, 2009 ; Haller et al, 2016 ; Fällmar et al, 2017 ; Riederer et al, 2018 ) in many brain regions. In this study, we also observed CBF and microstructural abnormalities in the Hip, PCC, Pr, OLWM, DT, FLWM, and CNC regions in patients with aMCI, a finding that agrees with findings from the previous study describing the association of changes in these regions with the likelihood of AD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We may be able to further disentangle questions of orientation coherence (dispersing and “kissing” fibers), fiber diameter, fiber density, membrane permeability, and myelination, which all influence classic anisotropy and diffusivity measures derived from DTI. Several AD studies have already used multi-shell protocols to compute diffusion indices from models that do not assume mono-exponential decay, such as diffusion kurtosis imaging (DKI; Jensen et al, 2005; Chen et al, 2017; Cheng et al, 2018; Wang M.-L. et al, 2018), and multi-compartment models such as neurite orientation dispersion and density imaging (NODDI; Zhang et al, 2012; Colgan et al, 2016; Slattery et al, 2017; Parker et al, 2018). To date, approximately 20 participants in ADNI have been scanned with multi-shell diffusion protocols; in a future report, we will relate multi-shell measures to those examined here.…”
Section: Discussionmentioning
confidence: 99%
“…We may be able to further disentangle questions of orientation coherence (dispersing and 'kissing' fibers), fiber diameter, fiber density, membrane permeability, and myelination, which all influence classic anisotropy and diffusivity measures derived from DTI. Several AD studies have already used multi-shell protocols to compute diffusion indices from models that do not assume monoexponential decay, such as diffusion kurtosis imaging (DKI; Jensen et al, 2005;Chen et al, 2017;Cheng et al, 2018;, and multi-compartment models such as neurite orientation dispersion and density imaging (NODDI; Zhang et al, 2012;Colgan et al, 2016;Slattery et al, 2017;Parker et al, 2018). To date, approximately 20 participants in ADNI have been scanned with multishell diffusion protocols; in a future report, we will relate these measures to those examined here.…”
Section: Discussionmentioning
confidence: 99%